The Puzzle of Financial Leverage Clienteles - SARIG, ODED; SCOTT, JAMES (Journal of Finance, 1985)
ABSTRACT Empirically, it appears that common stock of publicly traded corporations with high‐debt ratios tends to be held by investors with relatively low marginal taxes while the stock in companies with little debt is held by investors in high‐tax brackets. A number of authors have argued that in an equilibrium similar to the one described by Miller [8], these clienteles should exist. We argue that standard portfolio theory does not imply financial leverage clienteles for publicly traded firms. We explain the empirical relationship between investor tax rates and leverage ratios by the existence of dividend clienteles and a positive relationship between dividend yield and leverage ratios.